Commodified care work in European Labour Markets - Ungerson, Clare [Verfasser] (My University, 2003)
"This paper considers the reasons why a form of commodified care work identified as 'routed wages' has developed in many European countries over the past decade. These systems, which are often argued for within an empowerment discourse for the care users, are not often considered in terms of their labour market impact. The paper uses empirical data generated in a cross-national qualitative study of care users and their care givers in five European countries (Austria, France, Italy, The Netherlands and the UK) to outline the different ways in which different types of commodified care schemes impact on the labour market. It is suggested that the schemes differ in their labour market impact, depending on whether or not the scheme is regulated, and on the geographic, social and economic contexts within which the scheme is implemented." (author's abstract, IAB-Doku) ((en))
Keywords: S 4 Kosten & Finanzierung; G 1.2.2 Beschäftigungs- und Arbeitsverhältnisse; G 2.3.2 Arbeits- & Beschäftigungsverhältnisse; G 2.4.3 Privater & Familiärer Wandel; G 2.3.4 Qualifikationswandel; I 2.2.1 Westeuropa; Pflegetätigkeit; Finanzierung; Pflegeberuf; Care work; Arbeitsverhältnis; Haus- und Familienpflege; Beschäftigungseffekte; Internationaler Vergleich; Menschen mit Behinderung; Arbeitgeber; Österreich; Frankreich; Italien; Niederlande; Großbritannien